Colonization by oligochaetes (Annelida: Clitellata) in decomposing leaves of Eichhornia azurea (SW.) Kunth (Pontederiaceae) in a neotropical lentic system - Martins, Renato Tavares; Silveira, L. S.; Alves, R. G. (Annales de Limnologie, 2011)
The objective of the present study was to examine the colonization of oligochaetes during the decomposition of leaves of the macrophyte Eichhornia azurea in a lentic system in southeastern Brazil. The experiment was conducted between September and November 2007, with the use of 21 nylon bags measuring 15×15 cm with 2 mm mesh, each containing 10 g of dried leaves. The bags were removed from the lake after 2, 5, 8, 12, 25, 45 and 65 days. At the end of the experiment, 31.40% of the initial mass remained, and the decomposition rate was 0.018 d -1. The mean density of oligochaetes during the experiment was 32.81±9.58 ind.g -1 DM. The sub-families Naidinae and Pristininae accounted for 99.83% of the oligochaetes. The substrate quality influenced the colonization of E. azurea leaves, as observed from the cluster analysis by the formation of two groups based on increased density during the experiment, indicating a degradative ecological succession. During the decomposition there were changes in the community of oligochaetes, resulting from differences in the ability to exploit various food sources, with predominance of predators in the first decomposition phase and of collectors at the end of the experiment. © 2011 EDP Sciences.
Keywords: Annelid; Aquatic Plant; Cluster Analysis; Colonization; Community Dynamics; Decomposition; Dominance; Experimental Study; Lentic Environment; Macrophyte; Neotropical Region; Substrate; Succession; Annelida; Clitellata; Eichhornia; Eichhornia Azurea; Oligochaeta (metazoa); Pontederiaceae